21 Increased dietary isoleucine enhances lipogenesis and fat accumulation in skeletal muscle through depressing AMPK phosphorylation in pigs. (7th December 2018) - Yin, J
Abstract: Herein we review the research on the extended use of supplemental amino acids (AA) for monogastric animals and attempt to provide a rationale for specific AA. Recent advances on animal nutrition have resulted in opportunities to enable the minimum supply of nutrients for maximum growth of livestock. For example, feed formulation technology using ideal protein concept contributes to improving protein digestion and absorption and productive performance. The use of supplemental AA, particularly Lys, Met, and Thr, the most limiting AA in swine and poultry, has enhanced the economic feasibility of feeds by reducing the use of high-priced protein supplements and increasing the use of economical carbohydrate ingredients without affecting dietary crude protein concentration. In addition to these AA, continuing efforts on animal nutrition have revealed new knowledge on diverse physiological functions as well as optimum nutritional requirements of Val and Arg in swine and broiler, respectively. In fact, the addition of dietary Val in lactating sow diets decreased backfat loss by increasing feed intake, while supplementing Val in piglets was found to increase average daily gain by activating mRNA expression of branched chain AA metabolic enzymes in the liver. On the other hand, Arg supplementation increased carcass yield by decreasing abdominal fat deposition and bone mineral formation in broiler chickens. Although we reported positive effects of these supplemental AA on production, we have yet to explore the effects of the AA supplementation on gut health and environmental impacts. With the increase in fluctuation in the feed prices for livestock producers and the public concerns about animal welfare, safe animal product consumption, and environmental stewardship, use of supplemental AA may play increasingly important roles in the future.